Test results of the resonant single-wire power transmission system for induction heating of the switch rail - D. V. Ermolenko; L. Yu. Yuferev; O. A. Roshchin (Вестник Научно-исследовательского института железнодорожного транспорта)
The article provides results of tests of a resonant single-wire power transmission system for induction heating of a switch rail in the organization of train traffic in difficult winter climatic conditions.Laboratory tests have shown the possibility and feasibility of applying heating by an induction method based on a resonant system for transmitting electricity at an increased frequency. Induction heating occurs in the metal due to the excitation of electric currents by an alternating electromagnetic field. With induction heating, only the conductive body is heated, and not the heating element. In the surface layer, called the penetration depth, 86 % of the total power is released, which saves energy. At resonance, active and reactive energy is used.In the experiment a resonant single-wire system for transmitting electrical energy was used to power the induction heaters of the switch rail. Electrical and thermal parameters of the induction heating system were measured. Its advantages over the rail heating system with tubular electric heating elements (TEH) are considered. Developed equipment operates according to the principle of “direct heating”, which allows to increase the heating rate or reduce electricity consumption at the same heating rate as compared to TEH. It is possible to use one power converter for several swi tches. Due to its higher heating temperature combined with relatively low power consumption, it is suitable for use in the northern regions. Developed equipment is connected to AC network with a voltage of 380 V and 50 Hz, operating frequency range is 6–10 kHz, power consumption for heating a single object is 6–20 kW, and the voltage on the transmission line is less than 1 kV.